2004
DOI: 10.1089/089771504322778677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perineurial Window Size on Nerve Regeneration, Blood–Nerve Barrier Integrity, and Functional Recovery

Abstract: End-to-side neurorrhaphy is used clinically to reconstruct nerve injuries when the lack of a suitable proximal nerve stump precludes conventional approaches to microsurgical repair. In end-to-side neurorrhaphy, the distal stump of a transected nerve is sutured to the side of an intact nerve that serves as an axon donor. Prior studies suggest that this perineurial window is a prerequisite for effective nerve regeneration into the recipient nerve. However, the optimal size for this perineurial window remains unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 32 publications
2
24
0
3
Order By: Relevance
“…In fact, when there is no injury to the donor nerve, nerve regeneration can occur following endto-side anastomosis, but several experimental studies have shown that when the donor nerve had a fenestration, the effect of nerve regeneration was better [71][72][73][74]. Although there are still controversies over whether fenestration can damage the donor nerve, many studies have confirmed that the fenestration of the epineurium can cause a slight damage to the donor nerve, but does not affect the donor nerve function [75][76][77]. this approach does not cost the donor function when nerve grafting.…”
Section: Epineurium or Perineurium Windowmentioning
confidence: 99%
“…In fact, when there is no injury to the donor nerve, nerve regeneration can occur following endto-side anastomosis, but several experimental studies have shown that when the donor nerve had a fenestration, the effect of nerve regeneration was better [71][72][73][74]. Although there are still controversies over whether fenestration can damage the donor nerve, many studies have confirmed that the fenestration of the epineurium can cause a slight damage to the donor nerve, but does not affect the donor nerve function [75][76][77]. this approach does not cost the donor function when nerve grafting.…”
Section: Epineurium or Perineurium Windowmentioning
confidence: 99%
“…The idea is that the axons of the healthy nerve create lateral sprouts that grow inside the damaged one. Although axons can travel in the epineurial space of rabbit nerves [18], in humans the epineurial window is essential to achieve axonal regeneration [68]. Sensory axons will spontaneously sprout from the healthy into the injured nerve, providing a kind of protective sensation, although it is never fully normal [11,65,66].…”
Section: End-to-end Anastomosismentioning
confidence: 99%
“…16,51,53,64 Interestingly, if epineurial or perineurial windows were enlarged from 1 to 4 or 5 mm, respectively, then, also, the magnitude of axonal ingrowth into the recipient nerve was increased. 65,66 Subepineurial focal degeneration and demyelination of the donor nerve distal to the site of coaptation in experimental groups Notably, bimodality coefficient > 0.555 indicates that a distribution is bimodal 56 (but see Jackson, P.R., Tucker, G.T., and Woods, H.F. (1989). Testing for bimodality in frequency distributions of data suggesting polymorphisms of drug metabolism -hypothesis testing.…”
Section: Kovač Ič Et Almentioning
confidence: 99%